Gangguan kecemasan OCD: Penyebab dan faktor resiko pada remaja - Agung, Mirza Aaliyah (Maliki Interdisciplinary Journal, 2023)
OCD (Obsessive-Compulsive Disorder) in adolescents is an anxiety disorder characterized by obsessive disturbing thoughts and the urge to perform compulsive actions repeatedly. This study aims to investigate OCD in adolescents by focusing on the causes and risk factors that contribute to this disorder. The research method used is library research which is described descriptively. The results showed that OCD in adolescents involves disturbing obsessive symptoms such as excessive cleanliness, order, health, religion, or morality, followed by recurrent compulsions. This disorder can cause decreased academic performance, difficulties in social relationships, high stress levels, and limitations in participating in daily activities in affected adolescents. Effective treatment approaches for OCD in adolescents, such as cognitive behavioral therapy (CBT), exposure and response prevention therapy (ERP), and the use of medications such as selective serotonin reuptake inhibitors (SSRIs).